Calcium and vitamin D supplementation do not influence menopause-related symptoms: Results of the Women's Health Initiative Trial. Issue 3 (July 2015) - LeBlanc, Erin S.; Hedlin, Haley; Qin, FeiFei; Desai, Manisha; Wactawski-Wende, Jean; Perrin, Nancy; Manson, JoAnn E.; Johnson, Karen C.; Masaki, Kamal; Tylavsky, Frances A.; Stefanick, Marcia L.
Highlights: Women on calcium/vitamin D did not have fewer menopausal symptoms than placebo women. Calcium/vitamin D was not associated with sleep quality, mental health, or fatigue. Calcium/vitamin D did not improve wellbeing in women with an average age of 64 years. Abstract: Background: It is unknown whether supplementation with calcium and vitamin D has an impact on menopause-related symptoms. Methods: As part of the Women's Health Initiative Calcium/Vitamin D Supplementation Trial (CaD), women were randomized at 40 clinical sites to elemental calcium carbonate 1000 mg with vitamin D 400 IU daily or placebo. At the CaD baseline visit (year 1 or year 2) and during a mean follow-up of 5.7 years, participants provided data on menopause-related symptoms via questionnaires. Generalized linear mixed effects techniques were used to address research questions. Results: After excluding participants with missing data ( N = 2125), we compared menopause-related symptoms at follow-up visits of 17, 101 women randomized to CaD with those of 17, 056 women given the placebo. Women in the CaD arm did not have a different number of symptoms at follow-up compared to women taking the placebo ( p = 0.702). Similarly, there was no difference between sleep disturbance, emotional well-being, or energy/fatigue at follow-up in those who were randomized to CaD supplementation compared to those taking the placebo. Conclusions: Our data suggest that supplementation with 1000 mg of calcium plus 400 IU of vitamin D does not influence menopause-related symptoms over an average of 5.7 years of follow-up among postmenopausal women with an average age of 64 at the WHI baseline visit.